Fight club - Fincher, David; Norton, Edward; Palahniuk, Chuck; Pitt, Brad, 1963-; Uhls, Jim; Bonham Carter, Helena, 1966- (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 2002)
A confused young man tired of his life finds a new one in a new club where you beat each other to a plup as therapy.
Features: commentary by David Fincher, or David Fincher with Brad Pitt, Edward Norton, and Helena Bonham Carter, commentary with screenwriter and novelist, commentary by special effects crew.
Based on the novel by Chuck Palahniuk.
Brad Pitt, Edward Norton, Helena Bonham Carter, Meat Loaf Aday, Jared Leto.
MPAA rating: R.
DVD, Dolby digital 5.1 surround.
Closed-captioned.
Keywords: Clubs -- Drama; Palahniuk, Chuck -- Film and video adaptations; Fighting (Psychology) -- Drama; Video recordings for the hearing imapired; Based on the book; Feature films